Trends in E-Learning 2018
DOI: 10.5772/intechopen.74843
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of E-learning in South Africa

Abstract: The University of South Africa (UNISA) is the largest open distance e-learning (ODeL) university in the continent of Africa, with a student headcount more than 300,000. Over two decades after the transition from apartheid to democracy, vast inequalities across race, class, gender and socio-economic status persist in South Africa, with the majority of the African people being the most affected. Demographically, the African people constitute about 80.8% of the country's total population, compared to whites, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 14 publications
0
47
1
Order By: Relevance
“…Academics have expressed their dissatisfaction about this level of Internet access in the university for both staff and students, but the university lacks the proper wireless network infrastructure to support the teaching and learning processes on the university's LMS. This current finding contradicts the findings of Letseka and Pitsoe (2014), as well as those of Letseka et al (2018) who presented the University of South Africa as the largest university in Sub-Saharan Africa based on its ability to efficiently utilise the LMS as a medium to achieve virtual teaching and learning. This study revealed that the academics at the university studied have resorted to accessing the internet privately, which corroborates the findings of Coleman and Mtshazi (2017); Govender andGovender (2014) Letseka (2001); as well as Ogunrewo and Odusina (2010), who all noted that academics in African HEIs personally sourced private Internet connections when faced with serious difficulties accessing the Internet on campus.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Academics have expressed their dissatisfaction about this level of Internet access in the university for both staff and students, but the university lacks the proper wireless network infrastructure to support the teaching and learning processes on the university's LMS. This current finding contradicts the findings of Letseka and Pitsoe (2014), as well as those of Letseka et al (2018) who presented the University of South Africa as the largest university in Sub-Saharan Africa based on its ability to efficiently utilise the LMS as a medium to achieve virtual teaching and learning. This study revealed that the academics at the university studied have resorted to accessing the internet privately, which corroborates the findings of Coleman and Mtshazi (2017); Govender andGovender (2014) Letseka (2001); as well as Ogunrewo and Odusina (2010), who all noted that academics in African HEIs personally sourced private Internet connections when faced with serious difficulties accessing the Internet on campus.…”
Section: Discussioncontrasting
confidence: 99%
“…Among the various HEIs in developing counties, especially in Sub-Saharan Africa, development and the incorporation of multimedia into course content, pedagogical strategies and learners' different learning styles are some of the challenges associated with the uptake and usage of an LMS (Kebritchi et al, 2017). Of note is the fact that the University of South Africa has overcome these challenges to a large degree as it has fully trained and equipped its academics for virtual teaching and learning activities and it currently boasts of being the largest university in Africa, with over 350,000 students who are registered on their LMS (Letseka & Pitsoe, 2014;Letseka et al, 2018;Ngubane-Mokiwa, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, students from poor rural areas face challenges such as lack of or no network coverage, lack of or irregular supply of electricity supply and no academic support at home (Ogina & Mampana, 2013;Singh, 2015;Faroa, 2017;Letseka, Letseka, & Pitsoe, 2018). Simelteonously, the universities have to capacitate academics and tutors with an understanding of digital learning and provide resources and infrastructure for the use of Information and Communications Technology to deliver teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Against the background of such challenges, it remains challenging and problematic for higher education institutions to advocate a fully online teaching and learning approach, while against the background of challenges to e-learning integration and adoption in higher education for a substantial period of time. Few South African universities have been implementing blended learning to increase access and improve learning (Singh, 2015;Letseka, Letseka, & Pitsoe, 2018;Nyawo & Mashau, 2019). Few universities had intentions for their direct tuition to be entirely replaced by online teaching and learning.…”
Section: Introductionmentioning
confidence: 99%
“…One's individuality is constituted through one's relationships with others, expressed in the Nguni languages as 'umuntu ngumuntu ngabantu' ('a person is a person through others'). 51 justice. Most pertinent to this discussion, is its potential to 'illuminate the always thorny problem revealed when individual interests collide with public interests'.…”
mentioning
confidence: 99%